Konstruksi Kebahagiaan Ibu: Psikoedukasi Berbasis Psikologi Positif dan Nilai Islam untuk Mengatasi Social Comparison serta Mitos Perfect Mom - Hilda Fadhilah (Indonesian Journal of Educational Counseling, 2026)
Cultural pressure on mothers in the digital era is intensifying through mechanisms of social comparison and the "perfect mom" narrative on social media. However, most conventional psychological studies still tend to document the pathological side of parenting rather than exploring strategies for building mothers' psychological well-being. This article aims to fill this gap by analyzing the construction of maternal well-being through a positive psychology perspective specifically the PERMA model and the Subjective Well-Being framework integrated with Islamic domestic-educational values in emotion regulation. The method used is a narrative-synthetic literature review of scientific articles from the Scopus, Web of Science, and Google Scholar databases for the period 2015–2025. Article selection was based on keywords including maternal well-being, positive psychology, social comparison, perfect mom, and Islamic parenting values, with inclusion criteria of peer-reviewed articles in English or Indonesian that address protective aspects of maternal well-being. The synthesis analysis was conducted thematically to group patterns of well-being construction across studies. The synthesis of the literature indicates that maternal well-being is not formed individually but is shaped by relational, cultural, and spiritual interactions. Mothers who are able to interpret their domestic role as a field of worship and an educational mandate tend to show a more adaptive resilience profile in the reviewed literature. The theoretical contribution of this article is the proposed Maternal Flourishing Model (MFM) as a foundation for strength-based psychoeducational interventions in family counseling and positive psychology counseling services in Indonesia